A pyroptosis-related gene model and its correlation with the microenvironment of lung adenocarcinoma: A bioinformatics analysis and experimental verification - Dong, Yi; Yi, Lina; Song, Qibin; Yao, Yi (Frontiers in Genetics, 2022)
Background: Non-small cell lung cancer, comprising lung adenocarcinoma (LUAD) and lung squamous cell carcinoma, is one of the leading causes of cancer-related mortality. Pyroptosis is a new form of programmed cell death involved in cancer development. The relationship between LUAD and pyroptosis is unclear. This research aims to investigate this relationship and develop a stratified clinical model based on pyroptosis-related genes (PRGs). Methods: We analyzed the data of LUAD from The Cancer Genome Atlas (TCGA) and evaluated the expression of 48 PRGs to identify the differentially expressed genes. Then, constructing the risk model using the least absolute shrinkage and selection operator and the Cox regression method to find the gene signatures. The functional enrichment, immune cell infiltration, tumor mutational burden (TMB), and expression of immune checkpoints were compared to investigate the potential mechanism. The IC50 of common drugs was evaluated and compared. The inflammasome activation assay and lactate dehydrogenase (LDH) assay of NLR-family CARD-containing protein 4 (NLRC4) were also performed to confirm the role of pyroptosis in LUAD. Results: The pyroptosis-related model accurately predicted the prognosis of patients with LUAD, with the low-risk group exhibiting a higher survival probability. The risk score was an independent prognostic factor for survival. The stratified patients exhibited distinct tumor microenvironments, TMB, and drug sensitivity. The validation experiments of NLRC4 confirmed its role in inducing pyroptosis via promoting IL-1 maturation.